Oil-stock Nexus in an Oil-rich Country: Does Geopolitical Risk Matter in Terms of Investment Horizons?. Issue 4 (19th May 2021) - Aloui, Chaker; Hamida, Hela Ben
ABSTRACT: In this paper, we attempt to delineate the relevance of geopolitical risk in the oil-stock nexus in a time-frequency domain. We resort to various wavelet coherence methods to capture the influence of geopolitical risk on the dynamic association between oil and stock prices in Saudi Arabia as a rich oil-exporting country in a region with high geopolitical risk. We primarily show that the role of geopolitical risk in the oil-stock interplay varies through timescales and investment horizons. News regarding geopolitical tensions affects the stock market in high frequency bands, while oil impacts are manifested more on longer time-horizons. Geopolitical risk weakens oil-stock connectedness in the short term. Interestingly, geopolitical incidents significantly lower the oil-stock magnitude and volatility correlation. These results offer prominent insights for investors and policy makers, which may be beneficial when responding to future geopolitical tensions in terms of risk management and the identification of investment opportunities.